TINJAUAN YURIDIS TERHADAP TANAH HAK MILIK BERSAMA SEBAGAI AGUNAN DALAM PERJANJIAN KREDIT DI BANK BERDASARKAN UNDANG-UNDANG NOMOR 4 TAHUN 1996 - I Made Sudirga; Made Emy Andayani Citra (Jurnal Hukum Saraswati (JHS), 2019)
The purpose of this study was conducted to determine the legal effects that arise in pledging the land of common property rights as collateral in the Bank in terms of Law No. 4 of 1996 on Encumbrance Right Over Land And Land Related Objects. This research method using normative research method by reviewing the Law No. 4 of 1996. Data analysis is done to solve the problems contained in the problem formulation by using descriptive qualitative data analysis. From this study obtained the result that the land of common property rights may be assumed that the land is owned by more than one person whose names are listed in the land title certificate as the land owner. the land is owned by more than one person and there is no clear division, then the authorities to take legal action on the land are all three together. Therefore,the legal effect is the existence of the consent of the other party by giving a special power of attorney to such person to act for and on their behalf to pledge the land.